Effectiveness and safety of azvudine versus nirmatrelvir-ritonavir in adult patients infected with COVID-19 omicron strains: a retrospective study in Beijing - Huaiya Xie; Yaqi Wang; Yan Xu; Luo Wang; Junping Fan; Siqi Pan; Chuan Shi; Xiaoyan Liu; Xiaoxing Gao; Xiaobei Guo; Siyuan Yu; Jia Liu; et al. (Scientific Reports)
Abstract The study was to evaluate the clinical outcomes of azvudine versus nirmatrelvir-ritonavir against omicron strains of coronavirus disease 2019 infections and determine their comparative effectiveness. This retrospective study included 716 patients who received nirmatrelvir-ritonavir (NR group) or azvudine (FNC group) at Peking Union Medical College Hospital between 1 November 2022 and 27 February 2023. Patients in the FNC group (n = 304) were younger, exhibited less severe symptoms, started antiviral therapy later, received corticosteroids more frequently, and used tocilizumab less frequently than patients in the NR group (n = 412). Within 28 d of therapy, 40 (9.7%) and 20 (6.6%) deaths were in the NR and FNC groups, respectively. No differences were observed between drugs and mortality rates (odds ratio [OR] 0.78, 95% CI 0.40–1.5, P = 0.45), clinical improvement (OR 0.79, 95% CI 0.79–1.3, P = 0.38), and clinical progression (OR 1.0, 95% CI 0.58–1.8, P = 0.96). More patients in the NR group experienced platelet decline than those in the FNC group (17.6% vs. 8.9%, P = 0.034). This study indicated that the effectiveness and safety of azvudine were comparable to those of nirmatrelvir-ritonavir.